BIMBINGAN BELAJAR ANAK-ANAK DESA PILANGSARI MELALUI SOCIAL APPROACH BERBENTUK REWARD SEBAGAI MOTIVASI BELAJAR - Khudriyah; Muhammad Hasan Alkaff; Moh. Syamsudin; Aqibah; Nuniek Rahmatika (UI Cirebon (Universitas Islam Cirebon), 2023)
Based on observations during the Cirebon Islamic Institute of Religion Student Work Lecture in Pilangsari Village, it was found that some children were lazy in participating in class learning because they had difficulty with some of the material being taught. The purpose of this service is to overcome these problems by providing motivation that can build enthusiasm for learning the children of Pilangsari Village, RT. 02 RW. 04 through the provision of rewards as a form of appreciation in order to maximize their learning potential. The method used is a social approach method in the form of cooperation and varied learning methods by holding guidance activities or joint learning forums and children's creativity events through various competitions. After the activity was carried out, an analysis and evaluation was carried out, it appeared that the children experienced an increase in talent and interest in the fields of education and the arts. This activity received a good response, as seen from the enthusiasm of the children in participating in the tutoring and competitions held.